IMPLEMENTASI AUGMENTED REALITY (AR) UNTUK MEMBANTU SISWA BELAJAR GEOMETRI DIMASA PANDEMI DI SMPN 1 SINDANG - Diana Hardiyanti; Rosyadi Rosyadi; Mellawaty Mellawaty (Integral : Pendidikan Matematika, 2020)
BSTRACTS The purpose of this study was to determine the process of learning geometry using the mobile application Augmented Reality (AR) in junior high school students during the pandemic, and to find out the process of using the Augmented Reality (AR) mobile application to help students learn geometry, and to determine the extent of students' understanding of the material. cubes and blocks. This type of research is qualitative with grade IX student participants in one of the junior high schools in Indramayu in the 2020/2021 school year. From these participants, 4 students were taken as respondents, because this year the corona virus outbreak was rife so it was not allowed to crowd too many people. The selection of respondents used a purposive sampling technique. Based on data collection techniques and data analysis through observation, interviews, tests, documentation, and field notes. The following conclusions were obtained: The process of learning geometry using the Augmented Reality mobile application in grade IX students received good responses from students, teachers and parents because it can help students learn geometry, and increase students' understanding in geomery learning, which initially students do not know the kinds of kinds of building space after using the Augmented Reality mobile application students can find out even students can describe it. In learning cubes and blocks in grade IX students, namely students are more interested in learning using three-dimensional media because students can be invited to learn while playing, so that students are more active in learning. So it can be concluded that the use of the Augmented Reality mobile application can help students learn geometry. Keywords: Augmented Reality (AR), Geometry Learning ABSTRAK Tujuan penelitian ini untuk mengetahui proses pembelajaran geometri menggunakan aplikasi mobile Augmented Reality (AR) di siswa SMP dan untuk menggetahui proses penggunaan aplikasi mobile Augmtended Reality (AR) dapat membatu siswa belajar geometri, dan untuk mengetahui sejauh mana pemahaman siswa pada materi kubus dan balok. Jenis penelitian ini adalah kualitatif dengan partisipan siswa kelas IX di salah satu sekolah negeri menengah pertama yang ada di Indramayu tahun pelajaran 2020/2021. Dari partisipan tersebut diambil 5 siswa sebagai responden, karena pada tahun ini maraknya wabah virus corona sehingga tidak diperbolehkan berkerumun terlalu banyak orang. Pemilihan responden tersebut menggunakan teknik purposive sampling. Berdasarkan teknik pengumpulan data dan analisis data melalui observasi, wawancara, tes, dokumentasi, dan catatan lapangan. diperoleh kesimpulan sebagai berikut: Proses pembelajaran geometri menggunakan aplikasi mobile Augmented Reality pada siswa kelas IX mendapatkan respon baik dari siswa, guru, karena dapat membantu siswa dalam belajar geometri, dan menambah pemahaman siswa dalam pembelajaran geomeri, yang awalnya siswa belum mengetahui macam-macam bangun ruang setelah menggunakan aplikasi mobile Augmented Reality siswa dapat mengetahuinya bahkan siswa dapat mendeskripsikannya. Pada pembelajaran kubus dan balok pada siswa kelas IX yaitu siswa lebih tertarik dalam pembelajaran menggunakan media tiga dimensi karena siswa dapat diajak belajar sambil bermain, sehingga siswa lebih aktif dalam pembelajaran. sehingga dapat disimpulkan penggunaan aplikasi mobile Augmented Reality dapat membantu siswa belajar geometri. Kata kunci: Augmented Reality (AR), Pembelajaran Geometri